Investigation of laser deposited multi-element oxides as an efficient catalyst for oxygen evolution reaction - Tan, Fabien Kiat Hao (Nanyang Technological University, 2022)
In the 21st century, a critical challenge met by research is to meet the increase of energy consumption in a growing world population. This strengthens the drive for a low cost, nonnoble and high-performance catalyst for OER in water splitting. Laser synthesis and processing of colloids (LSPC) has been identified as a suitable and expandable method for the synthesis of ligand-free nanomaterials in sealed environments. The advantages of using LSPC not only amounts to having high-purity surface of LSPC-generated nanoparticles, but also provides high throughput, convenience for preparing alloys or series of doped nanomaterials, and its continuous operation mode hence, making it suitable for downstream processing. In this report, we investigated the OER activity of laser deposited Co-Ni oxide onto carbon fiber substrate with varying ratios. Thermionic scanning electron microscopy (SEM, JOEL JSM 5500) and X-ray diffraction (XRD, Bruker, D8 Advance) was used to characterize the surface morphology and determine the crystal structure of the synthesized Co-Ni oxide. The Co-Ni oxide with the ratio of 5-5 is the best performing catalyst with the highest OER activity and excellent cycling stability among all the other samples.